Pearl Harbor payback (New York Good Times Home Video, 2001)
The Japanese raid on Pearl Harbor united all Americans against a common for, and from that day forward they spared nothing in order to mobilize against the menace that continued to threaten them in then Pacific. Also included are Target Tokyo, a 1945 documentary narrated by Ronald Reagan, which follows the first bombing raid on Tokyo by B-29 superfortresses and another World War II short film, Air War Against Japan.
Includes Appointment in Tokyo.
In English.
Keywords: World War, 1939-1945 -- Motion pictures and war